HIV and Hepatitis C Virus Testing and Seropositivity Rates in Canadian Federal Penitentiaries: A Critical Opportunity for Care and Prevention. Issue 4 (1st August 2004) - De, Prithwish; Connor, Nancy; Bouchard, Françoise; Sutherland, Donald
Abstract : BACKGROUND: Incarcerated persons experience high rates of HIV and hepatitis C virus (HCV) infection, but little is known about the burden of these bloodborne viruses among federal penitentiary inmates in Canada. OBJECTIVES: The present study investigates rates of testing and seropositivity for HIV and HCV among inmates in all 53 Canadian federal penitentiaries. METHODS: A cross-sectional design using surveillance data on voluntary HIV and HCV antibody testing in 2002 were applied to estimate the rate of testing uptake and the rate of incident seropositive tests among new admissions to federal penitentiaries and resident inmates. Rates of testing and infection were further examined by sex and region. Seroprevalence of HIV and HCV was estimated from the number of cumulative positive tests to year-end. RESULTS: Of 7670 new admissions during 2002, 30% were tested for HIV and HCV. Test seropositivity rates in this group were 0.7% for HIV and 10% for HCV. Of the 12, 426 resident inmates, 28% were tested for HIV and 27% for HCV. Seropositivity rates in this group were 0.3% for HIV and 7% for HCV. Seroprevalence rates at year-end for 2002 were 2.0% for HIV and 26% for HCV and were substantially higher among women offenders (HIV: 3.7% of women, 1.9% of men; HCV: 34% of women, 26% of men). Variations in testing uptake and test seropositivity were observed across regions. CONCLUSIONS: The present study underscores the value of continued monitoring and evaluation of trends in HIV and HCV infection, which remain prevalent in federal penitentiaries. Higher rates of testing are warranted for at-risk inmates to improve early detection of infection and provide infected inmates with timely care and treatment. For those who remain free of infection, testing can provide the additional benefits of exposing inmates to health counselling and for the reinforcement of prevention messages. The period of incarceration is also a critical opportunity to link inmates with outside resources in preparation for release to the community.